Proceedings of dissemination seminar on drivers of agrifood system transformation in Odisha - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
The concept of food systems has evolved rapidly in recent years, with a more holistic approach gaining traction among scholars and policymakers. This new perspective encompasses all elements and activities related to food production, processing, distribution, preparation, and consumption, as well as the socioeconomic and environmental outcomes of these activities. Despite growing awareness, the global food system is under threat due to unsustainable practices and the current trajectory of agrifood systems drivers, which risk derailing the achievement of Agenda 2030 targets. Increasingly, international organizations, countries, and civil society groups are utilizing foresight exercises to explore alternative scenarios and pathways for more resilient and sustainable food systems.